Seawater carbonate chemistry and growth, survival, deformities of bay scallop larvae - Samuel J Gurr; Genevieve Bernatchez; Mark S Dixon; Lisa Keith; Deborah R Hart; Lisa Milke; Dylan H Redman; Louis V Plough; George Sennefelder; Sheila Stiles; David Veilleux; Gary H Wikfors; et al. (PANGAEA, 2025)
This dataset contains the discrete data on a laboratory experiment of larvae of the bay scallop, Argopecten irradians, and larval response to ocean acidification over multiple generations. The first generation of exposure to ocean acidification is the F1 generation, while the second generation of exposure is the F2 generation. The F1 generation larval experiment was conducted from July 26, 2021 through August 5, 2021 at the NOAA Milford Laboratory in Milford, Connecticut. All treatment levels had a replication of 5 per OA treatment. The F2 generation experiment was conducted from August 16, 2022 - August 30, 2022 and had 3 replicates per treatment. For each generation, larvae were sampled for shell deformities in the first 48 hours, and then growth and survival till metamorphosis were quantified. This effort was conducted in support of the research objectives of the NOAA Ocean Acidification Program (OAP). This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from National Centers for Environmental Information (see Source) by the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-09-17.